The emerging roles of Hedgehog signaling in tumor immune microenvironment - Wang, Juan; Cui, Baiping; Li, Xiaojie; Zhao, Xinyue; Huang, Taomin; Ding, Xiaolei (Frontiers in Oncology, 2023)
The Hedgehog (Hh) signaling pathway is pervasively involved in human malignancies, making it an effective target for cancer treatment for decades. In addition to its direct role in regulating cancer cell attributes, recent work indicates that it has an immunosuppressive effect on tumor microenvironments. An integrated understanding of these actions of Hh signaling pathway in tumor cells and tumor microenvironments will pave the way for novel tumor treatments and further advances in anti-tumor immunotherapy. In this review, we discuss the most recent research about Hh signaling pathway transduction, with a particular emphasis on its role in modulating tumor immune/stroma cell phenotypes and function, such as macrophage polarity, T cell response, and fibroblast activation, as well as their mutual interactions between tumor cells and nonneoplastic cells. We also summarize the recent advances in the development of Hh pathway inhibitors and specifically highlight nanobiomaterials for Hh pathway modulation. We suggest that targeting Hh signaling effects on both tumor cells and tumor immune microenvironments could be more synergistic for cancer treatment.